Efficacy and Long-Term Outcomes of Tacrolimus versus Cyclophosphamide and Mycophenolate Mofetil in the Management of Pediatric IgA Vasculitis Nephritis: A Cohort Study in Single-Center - Han Y; Yang F; Zhou L; Yang J; Yang Y; Wang Y; Qiu L; Zhang Y; Zhou J (Drug Design, Development and Therapy)
Yanxinli Han,* Fengjie Yang,* Lanqi Zhou, Jing Yang, Yuan Yang, Yi Wang, Liru Qiu, Yu Zhang, Jianhua Zhou Department of Pediatrics, Tongji Hospital, Tongji Medical College, Huazhong University of Science & Technology, Wuhan, Hubei Province, 430030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianhua Zhou, Department of Pediatrics, Tongji Hospital, Tongji Medical College, Huazhong University of Science & Technology, Wuhan, Hubei Province, 430030, People’s Republic of China, Tel +86 027 83662684, Email jhzhou99@qq.comPurpose: IgA vasculitis nephritis (IgAVN) is one of the most common secondary glomerulonephritis in children. Although guidelines have reached a consensus about the effectiveness of cyclophosphamide (CYC) in IgAVN, the recommendations regarding the use of tacrolimus (TAC) and mycophenolate mofetil (MMF) are still inconsistent. Studies have demonstrated that TAC is safe and effective in IgAVN. However, the impact of immunosuppressive agents on the long-term outcome remains ambiguous. Therefore, the objective of this study is to compare the effectiveness and long-term outcome of TAC, CYC, and MMF in combination with glucocorticoid in pediatric IgAVN.Patients and Methods: A retrospective analysis was conducted on children with grade II–V IgAVN by renal biopsy at Tongji Hospital from November 2011 to October 2021. The collected clinical, pathological, treatment and follow-up data were analyzed.Results: A total of 422 patients were eligible. Among them, 108 patients received glucocorticoid in combination with oral TAC, 143 with intravenous CYC, and 171 with oral MMF. The complete remission rate (CR) of TAC (25.9%/44.3%) was significantly higher than that of CYC (16.1%/36.4%) at 3 and 6 months. Additionally, mean absolute decrease in urine protein at 1, 3, and 6 months were significantly higher in TAC than that in CYC and MMF groups. Compared to CYC, TAC and MMF groups had significantly lower overall incidence of adverse events (60.2%, 65.7% vs 84.4%). Moreover, TAC and MMF group had a more favorable renal prognosis (grade A and B) and a significantly lower recurrence rate (17.9%, 23.9% vs 41.8%) than CYC.Conclusion: This study reveals that TAC can rapidly and effectively reduce proteinuria and achieve renal complete remission with fewer adverse effects. Moreover, TAC and MMF are more favourable for renal prognosis.Keywords: IgAVN, immunosuppressive agents, renal remission, tacrolimus, cyclophosphamide, mycophenolate mofetil, long-term outcome